Family Life in Central Italy, 1880-1910: Sharecropping, Wage Labor and Coresidence - Iacovetta, Franca (Labour / Le Travail, 1987)
This article reviews the book, "Family Life in Central Italy, 1880-1910: Sharecropping, Wage Labor and Coresidence," by David I. Kertzer.
Keywords: FAMILY Life in Central Italy: 1880-1910: Sharecropping, Wage Labor & Coresidence (Book); KERTZER, David I., 1948-; Nonfiction; REVIEWS; SHARECROPPERS; books